Condonation confusion - Schoeman-Malan, L. (Faculty of Law, University of the Free State, 2017)
Some problems have arisen with the interpretation of the formalities for the execution of wills in sec. 2(1) of the Wills Act 7 of 1953. The courts were given the power of condonation in sec. 2(3) of the Act to prevent wills from being declared invalid when some of the formalities had not been complied with. The provisions in sec. 2(3) appear to be controversial. The basic principles have become the subject of continuing debate through case law. The High Courts constantly disagree when they have to interpret the basic principles for the condonation of non-compliance with formalities. The reform envisaged by the legislator at the outset has not resulted in a satisfactory solution. Sec. 2(3) has been deliberated from every possible perspective. Despite Supreme Court of Appeal judgements on the interpretation of concepts such as ‘document’, ‘drafted or executed’ and ‘intention’, sec. 2(3), in its current form, can never provide for all possibilities. The more one analyses and discusses sec. 2(3), the more indistinguishable the interaction between the applicable principles becomes. This article discusses recent cases that have come before the Gauteng High Court in Pretoria, in which two vastly different sets of facts resulted in identical judgements on sec. 2(3). This inquiry reveals that practical challenges remain for the courts and it is concluded that urgent intervention by the legislature has become a necessity.
Keywords: Wills Act; Testamentary condonation; Execution of wills